An Analysis of Digital Literacy Skills of Elementary School Students - Savira, Salsabila Bulqis; Nuroh, Ermawati Zulikhatin (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study aims to analyze elementary students' digital literacy skills using Paul Gilster's digital literacy theory, which encompasses internet searching, hypertextual navigation, content evaluation, and knowledge assembly. The research employed a qualitative case study approach involving fifth-grade students at SD Muhammadiyah 3 Ikrom. Data were collected through classroom observations and in-depth interviews with three selected students. The findings indicate that students demonstrate basic abilities in accessing and using digital information, particularly in technical operations. However, their skills in evaluating and synthesizing information remain limited and underdeveloped. Therefore, instructional support is needed to strengthen students’ critical, reflective, and integrative thinking skills in the responsible and effective use of digital information in the learning process